Requirements for developing ethical leaderships in Vietnam - Thanh, Nguyen Hai; Quang, Nguyen Van (Universitas Negeri Padang, 2020)
Challenges associated with leadership practices are rapidly increasing, thereby assigning more qualities to leaders. One of the recent theoretical issues that interest many scholars is ethical leadership development, using industrial revolution 4.0. This method does not only follow the traditional leadership styles, rather it is associated with universal qualities such as respect, service, fairness, honesty, and responsibility. For communities, increasing assertions is one of the essential foundations used to help leaders influence their subordinates' actions. This means that ethical leadership is the motto of the spirit of service leadership, especially for Vietnam leaders, a country with a strong transformation from a planned economy to a socialist-oriented market. Therefore, leadership values need to be adjusted, supplemented, and developed to keep up with the Industrial Revolution's requirements 4.0.